Maternal Psychosocial Determinants and Stunting in a Socioeconomically Vulnerable Region of Eastern Indonesia - Elzina Dina De Fretes; Isra Nur Utari S Potabuga (Universitas Nahdlatul Ulama Surabaya, 2026)
Introduction: Stunting remains a persistent public health challenge in socioeconomically vulnerable regions, where behavioural and structural determinants interact to influence child growth outcomes. The relative contribution of maternal psychosocial factors within structurally constrained settings remains insufficiently understood. Purpose: This study examined the structural relationships between maternal self-efficacy, maternal social support, child feeding practices, and stunting in a stunting-prone area of Eastern Indonesia. Design/methods/approach: An analytic cross-sectional study was conducted among 233 mother–child dyads recruited through consecutive sampling at a primary health centre. Maternal self-efficacy, social support, and feeding practices were assessed using validated Likert-scale instruments. Stunting was defined as height-for-age Z-score below minus two standard deviations based on WHO Child Growth Standards 2006. Data were analysed using Partial Least Squares Structural Equation Modelling. Findings/results: Maternal self-efficacy and social support demonstrated limited explanatory power in predicting feeding practices and stunting. Structural relationships were weak, suggesting that psychosocial determinants alone may not substantially influence growth outcomes in structurally vulnerable populations. Conclusions: Behavioural constructs appear constrained by broader socioeconomic conditions. Effective stunting reduction strategies should integrate maternal-level interventions with systemic improvements in food security, sanitation, and social protection.